Isolated leukemic infiltration of peripheral nervous system. Issue 2 (23rd December 2014) - Wang, Tingzhong; Miao, Yuan; Meng, Yanli; Li, Ailin
ABSTRACT Introduction: Isolated leukemic infiltration of peripheral nerves without central nervous system involvement, or isolated neuroleukemiosis, is an extremely rare complication of leukemia. Methods: We report the case of a patient with isolated neuroleukemiosis and review the pertinent literature. Results: A man with a 12‐year history of acute monoblastic leukemia presented with median mononeuropathy. Magnetic resonance imaging revealed a thickened median nerve. Nerve biopsy confirmed the diagnosis of leukemic infiltration. Clinical resolution was achieved through local radiation. Only 10 cases of isolated neuroleukemiosis have been reported. Most were in remission from leukemia. Our patient is the only one who was considered clinically cured of leukemia. Conclusions: The presumed pathophysiology of isolated neuroleukemiosis is hematogenous spread of leukemic cells into the peripheral nervous system across the blood–nerve barrier. It should be considered in the differential diagnosis in patients with leukemia who present with neuropathy, even when they are considered to be clinically cured of leukemia. Muscle Nerve 51: 290–293, 2015